Demographic Dynamics and Urban Property Crime : A Linear Regression Analysis in Kuala Lumpur and Putrajaya (2015-2020) - Azizul, Ahmad; Tarmiji, Masron; Asykal Syakinah, Mohd Ali; Yoshinari, Kimura; Syahrul Nizam, Junaini (Planning Malaysia: Journal of the Malaysian Institute of Planners, 2024)
In an era where urbanization is rapidly transforming the landscape of cities, this study provides a crucial overview of how demographic shifts influence property crime in metropolitan areas. The paper delves into the complex interplay between property crime rates and demographic characteristics in the urban settings of Kuala Lumpur and Putrajaya, Malaysia, over six years from 2015 to 2020. Employing linear regression analysis, the study meticulously examines the relationship between property crime and various demographic factors, including total population, male and female populations, and residential and household densities. The findings indicate a consistent positive correlation between total population and property crime, emphasizing urban density's role in crime propensity. Notably, the male population shows a stronger correlation with property crime than females. The study also highlights how residential and household densities influence property crime in these urban settings. These insights are invaluable for policymakers and urban planners, guiding targeted strategies to reduce property crime in growing cities.